The Causality Between Energy Consumption and Carbon Emission in Indonesia - Lismiyah, Efi; Marselina, Marselina; Taher, Arvinia Ratih; Gunarto, Toto; Aida, Neli (Universitas Pasundan, 2024)
Energy as one part of the source of energy has a very important role as a pioneer of economic development in the activities of creation, distribution, and consumption. This research aims to identify the causes between energy consumption and carbon dioxide emissions in Indonesia. The type of research used is a quantitative research type which is analyzed using multivariate. The research results show that there is a relationship that is strong and 2-way proves that there is an increase in energy consumption which causes an increase in carbon dioxide emissions or other words an increase in energy consumption so that there is an increase in carbon dioxide emissions due to the large consumption of fossil fuels and thus an increase in carbon dioxide emissions will also be large considering that consuming fossil fuels can increase the increase in carbon dioxide emissions to a large extent. The research suggests the government needs to encourage energy efficiency through carrying out accelerated development of New Renewable Energy apart from that the government is starting to implement the use of environmentally friendly and renewable energy and improve public transportation facilities.